การศึกษาการขยายขนาดการผลิตพอลีอะลูมิเนียมคลอไรด์ในเครื่องปฏิกรณ์แบบปั่นกวน - ชุตินันท์ ชาญพานิชย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
This research investigated the influences of turbine’s type and mixing speed effect for scale-up of polyaluminum chloride synthesis in one liter reactor . It was found that the turbine’s type and speed affected rate of hydrolysis reaction and polymerization of polyaluminum chloride. Types of turbine and optimal speed found that to used turbine’s type pitched 6-blade turbine with mixing speed at 300 rpm ,percentage of polyaluminum chloride equal to 82.4 . Turbine’s type pitched 4-blade turbine with mixing speed at 600 rpm, percentage of polyaluminum chloride equal to 75.6 and Turbine’s type Rushton Turbine with mixing speed at 1800 rpm, percentage of polyaluminum chloride equal to 77 .In addition , turbine’s type pitched 6-blade turbine with mixing speed at 300 rpm were calculated size and mixing speed in the reactor of 10 and 25 liters. Each of experiments mixing speed is different cause by setting constant number of Reynolds number, impeller tip speed and Power per unit volume at n = 2, 1 and 0.66 respectively. Thus, the reactor size 10 liters with mixing speed 59,133 and 175 rpm and the reactor size 25 liters 33,99 and 144 rpm by turbine’s type pitched 6-blade turbine .The results shown percentage of polyaluminum chloride less than one liter reactor. So the relationship of the reactor size 1, 10 and 25 liters for the effect of percentage has to be similar to one liter reactor. Mixing speed is a major factor causing the outcome was similar. Determine the mixing speed provided by the relationship of n = 0.5, which is the speed at 200 and 173 rpm in reactors 10 and 25 liters, respectively, the experimental results shown that the effect of adjust mixing speed of reactors 10 and 25 liters. The results of percentage are close to one liter reactor. The percentage of reactor size 1, 10 and 25 liters is equal to 82.4, 82.3 and 82.2 respectively.